1999
DOI: 10.1038/6514
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by a caspase inhibitor in acute bacterial meningitis

Abstract: Half of the survivors of bacterial meningitis experience motor deficits, seizures, hearing loss or cognitive impairment, despite adequate bacterial killing by antibiotics. We demonstrate that the broad-spectrum caspase inhibitor N-benzyloxycarbonyl-Val-Ala-Asp-fluoromethyl-ketone (z-VAD-fmk) prevented hippocampal neuronal cell death and white blood cell influx into the cerebrospinal fluid compartment in experimental pneumococcal meningitis. Hippocampal neuronal death was due to apoptosis derived from the infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
169
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(183 citation statements)
references
References 29 publications
(29 reference statements)
8
169
0
6
Order By: Relevance
“…Z-VAD-FMK, a pancaspase inhibitor (36)(37)(38)(39)(40)(41)(42), can inhibit cell death in response to mechanical injury. Interestingly, our results showed that Z-VAD-FMK could inhibit chondrocyte death more effectively in chondroitinase ABC-treated explants than in control explants.…”
Section: Discussionmentioning
confidence: 99%
“…Z-VAD-FMK, a pancaspase inhibitor (36)(37)(38)(39)(40)(41)(42), can inhibit cell death in response to mechanical injury. Interestingly, our results showed that Z-VAD-FMK could inhibit chondrocyte death more effectively in chondroitinase ABC-treated explants than in control explants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, during the past 15 years, investigations have focused on the pathogenesis of meningitis-associated CNS complications (4). It has become clear that the development of these complications is not simply dependent on the presence of viable bacteria, but rather occurs as a consequence of the host inflammatory reaction to the pathogen (5). Although the exact mechanisms of immune activation in pneumococcal meningitis are unknown, recent in vitro experiments provide a clue.…”
Section: B Acterial Meningitis Caused By Streptococcus Pneumoniaementioning
confidence: 99%
“…However, a growing body of animal studies supports the hypothesis that a major pathophysiologic mechanism in sepsis is lymphocyte apoptosis (8 -11, 27). Recently, Braun et al (28) showed that administration of caspase inhibitors, drugs that block apoptosis, provided excellent neuroprotection in a rabbit model of pneumococcal meningitis. Ayala et al (29) reported that septic mice deficient in FasL gld had decreased mucosal B lymphocyte apoptosis and improved survival compared with controls.…”
Section: Lymphocyte Apoptosis: a Key Pathophysiologic Mechanism In Sementioning
confidence: 99%